1979
DOI: 10.1002/jez.1402100102
|View full text |Cite
|
Sign up to set email alerts
|

Development of acetylcholinesterase during embryogenesis of the ascidian Ciona intestinalis

Abstract: We have characterized the embryonic muscle cell cholinesterase of the solitary ascidian, Ciona intestinalis (L.). The effects of selective enzyme inhibitors and the inhibition of enzyme activity at high concentrations of substrate suggest that the muscle cell enzyme is an acetylcholinesterase (E.C. 3.1.1.7). After gastrulation and before hatching, acetylcholinesterase activity increased 35- to 40-fold; after hatching (18 hours postfertilization) this activity continued to increase, leveling off at about 36 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
21
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 17 publications
5
21
0
Order By: Relevance
“…The experiments using puromycin and Actinomycin D suggest that new RNA synthesis which begins sometime between the early and late gastrula stages is needed for the appearance of AchE activity (3,19,20,21). SATOH and IKEGAMI has suggested that the time of initiation of the enzyme development is determined by the clock mechanism closely associated with the DNA replication cycle (4, 5).…”
Section: Discussionmentioning
confidence: 99%
“…The experiments using puromycin and Actinomycin D suggest that new RNA synthesis which begins sometime between the early and late gastrula stages is needed for the appearance of AchE activity (3,19,20,21). SATOH and IKEGAMI has suggested that the time of initiation of the enzyme development is determined by the clock mechanism closely associated with the DNA replication cycle (4, 5).…”
Section: Discussionmentioning
confidence: 99%
“…Actinomycin D treatment begun before early gastrulation prevents enzyme formation but has less effect on the amount of enzvme activity produced the later it is added, finally causing no response when added after the middle tail formation stage (4,8 (12). Translationally active acetylcholinesterase mRNA was not found in RNA prepared from embryos before the 64-cell stage, but it was present in increasing amounts in RNA isolated from embryos between late gastrula and middle tail formation stages.…”
mentioning
confidence: 94%
“…Actinomycin D treatment begun before early gastrulation prevents enzyme formation but has less effect on the amount of enzvme activity produced the later it is added, finally causing no response when added after the middle tail formation stage (4,8 (11) have used such an assay in Xenopus oocytes to study acetylcholinesterase mRNA in rat brain and Torpedo electric organ RNA preparations. We modified their technique to include an immunoprecipitation step with antibody prepared against purified ascidian acetylcholinesterase (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meedel and Whittaker (17) have shown that increases in AcChoEase activity during the early stages of embryogenesis of the ascidian, Ciona intestinalis, are inhibited by actinomycin D and have suggested a possible role for mRNA production in the ontogeny of AcChoEase.…”
mentioning
confidence: 99%